Child in exile - Monika Mačkinová; Agnieszka Nowicka (Problemy Wczesnej Edukacji)
Migration, as a global phenomenon has a long history also in the Slovak Republic. Most of the migrants come, or are passing through its territory legally. There are still cases of illegal migration, too. The reasons for this form of state borders crossing are diverse. Part of illegal migrants are also people who are belonging to vulnerable groups, including unaccompanied minors. Since this is a specific and particularly vulnerable group of migrants, the European Union and subsequently the Slovak Republic adopted several legislative measures in the area of migration and asylum. Their aim is to adjust the status of unaccompanied minors and to contribute to finding lasting solutions to their current situation, taking into account their best interests.